Strategi Digital Fundraising Dalam Penghimpunan Dana Zakat: Studi Kasus Lembaga Amil Zakat Global Zakat - Sujanu Harto Mulyono; Qurroh Ayuniyyah; Ibdalsyah Ibdalsyah (Jurnal Ilmiah Ekonomi Islam, 2022)
This study analyzes the digital fundraising strategy in collecting zakat at the Global Zakat Amil Zakat Institute. The purpose of this study is to determine the digital fundraising strategy used by LAZ Global Zakat in supporting the collection of zakat funds and to formulate a digital fundraising strategy at LAZ Global Zakat. This study uses descriptive research methods with quantitative and qualitative study approaches. A case study approach to analyzing digital fundraising strategies in collecting zakat funds using SWOT Matrix analysis (Strengths, Weaknesses, Opportunities, Threats) and IE Matrix (Internal-External Matrix) and determining strategy using Quantitative Strategic Planning Matrix (QSPM). From these results, an implementation strategy is proposed. The results of this study are the digital fundraising strategy used by LAZ Global Zakat using two methods, namely organic (unpaid) and paid (paid). Digital fundraising strategies, both organic and paid, direct muzaki or prospective muzaki to the crowdfunding platform as a direct payment medium. Meanwhile, the formulation of the digital fundraising strategy for LAZ Global Zakat is to continue to use advertisements on the crowdfunding platform to offer zakat programs, collaborate with public figures or influencers to offer a joint ZIS program, create a ZIS program based on community preferences and improve automated answering applications related to zakat consultations that work 24 hours. Keywords: strategy, digital fundraising, zaka, global zakat